2012
DOI: 10.1089/nat.2012.0350
|View full text |Cite
|
Sign up to set email alerts
|

Uniqueness, Advantages, Challenges, Solutions, and Perspectives in Therapeutics Applying RNA Nanotechnology

Abstract: The field of RNA nanotechnology is rapidly emerging. RNA can be manipulated with the simplicity characteristic of DNA to produce nanoparticles with a diversity of quaternary structures by self-assembly. Additionally RNA is tremendously versatile in its function and some RNA molecules display catalytic activities much like proteins. Thus, RNA has the advantage of both worlds. However, the instability of RNA has made many scientists flinch away from RNA nanotechnology. Other concerns that have deterred the progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
92
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(92 citation statements)
references
References 177 publications
0
92
0
Order By: Relevance
“…Analysis of the 3WJ core structure provides a better understanding in the overall pRNA structure and multimerization, which are crucial for pRNA function. In recent years, RNA nanotechnology has emerged to play an important role in cancer therapy and disease treatment, serving as a vehicle to deliver therapeutics (Guo 2010;Guo et al 2012a). Studies on 3D structures of RNA lead to identifications of useful RNA motifs (Leontis et al 2006), which can be used to carry therapeutics for delivery (Shu et al 2011a(Shu et al , 2013aHaque et al 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of the 3WJ core structure provides a better understanding in the overall pRNA structure and multimerization, which are crucial for pRNA function. In recent years, RNA nanotechnology has emerged to play an important role in cancer therapy and disease treatment, serving as a vehicle to deliver therapeutics (Guo 2010;Guo et al 2012a). Studies on 3D structures of RNA lead to identifications of useful RNA motifs (Leontis et al 2006), which can be used to carry therapeutics for delivery (Shu et al 2011a(Shu et al , 2013aHaque et al 2012).…”
Section: Resultsmentioning
confidence: 99%
“…The unique features uncovered from the studies of phi29 pRNA include (1) independent folding of the ATPase gp16 interaction domain (Lee and Guo 2006) and the motor binding domain (Reid et al 1994a,b,c;Zhang et al 1994Zhang et al , 1995b and (2) the capacity to harbor and escort therapeutic functional modules without causing misfolding or loss of function of the incorporated functionalities. These special properties of phi29 pRNA have led to the development of this RNA as a novel vehicle for applications in nanotechnology and medicine (Hoeprich et al 2003;Guo et al 2005aGuo et al , 2006Guo et al , 2012aKhaled et al 2005;Guo 2010;Abdelmawla et al 2011;Shu et al 2011a,b,c;Shukla et al 2011;Zhou et al 2011). Recently, it was found that the core structure of phi29 pRNA, a 54-nt three-way junction (3WJ) (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The conjugation of nanoparticles with RNAi inducing agents has seen a substantial increase in interest in the last several years [42,60,62,121,135]. Briefly, RNA interference, or RNAi, is a process by which the expression of a gene can be silenced through the introduction of a double-stranded RNA (dsRNA).…”
Section: Some Examples Of Rna Nanoscaffold Functionalizationmentioning
confidence: 99%
“…Cytotoxicity to normal cells in relation to nanoparticles could be caused by size-related toxicity and the leaching of components. 129 Large-size nanoparticles can accumulate in the endoplasmic reticulum system. Further, the immunogenicity of nanoparticles can cause autoimmunity.…”
mentioning
confidence: 99%
“…Many different types of nanoparticles have been tested; each may have different side effects, and some side effects caused by nanoparticles may be fatal. 129 However, overall, the side effects of nanoparticles are not very well understood at present, and many more studies are needed.…”
mentioning
confidence: 99%